Occupational Physical Activity and Body Mass Index (BMI) Among Canadian Adults: Does Physical Activity at Work Help to Explain the Socio-economic Patterning of Body Weight? - Barberio, Amanda (Can J Public Health, 2011)
BACKGROUND: The behavioural and socio-cultural processes underlying the association between socio-economic position (SEP) and body mass index (BMI) remain unclear. Occupational physical activity (OPA) is one plausible explanatory variable that has not been previously considered. OBJECTIVES: 1) To examine the association between OPA and BMI, and 2) to examine whether OPA mediates the SEP-BMI association, in a Canadian population-based sample. METHODS: This cross-sectional study was based on secondary analysis of the 2008 Canadian Community Health Survey data, focusing on adults (age 25–64) working at a job or business (men, n=1,036; women, n=936). BMI was based on measured height and weight and we derived a novel indicator of OPA from the National Occupational Classification Career Handbook. Our analytic technique was ordinary least squares regression, adjusting for a range of socio-demographic, health and behavioural covariates. RESULTS: OPA was marginally associated with BMI in women, such that women with medium levels of OPA tended to be lighter than women with low levels of OPA, in adjusted models. No associations between OPA and BMI were detected for males. Baron and Kenny’s (1986) three conditions for testing mediation were not satisfied, and thus we were unable to proceed with testing OPA as a mediator. CONCLUSIONS: Notwithstanding the small effects observed in women, overall the associations between OPA and BMI were neither clear nor strong, which could reflect conceptual and/or methodological reasons. Future research on this topic might incorporate other plausible explanatory variables (e.g., job-related psychosocial stress) and adopt a prospective design.